2017
DOI: 10.15406/atroa.2017.02.00020
|View full text |Cite
|
Sign up to set email alerts
|

Role of Biological Scaffolds, Hydro Gels and Stem Cells in Tissue Regeneration Therapy

Abstract: Present review article emphasizes role of biological scaffolds, hydrogels and stem cells in tissue engineering mainly in regeneration or repairing of damaged tissues. Highly porous scaffold biomaterials are developed which act as templates for tissue regeneration and potentially guide the growth of new tissue. Present article also describes de-cellularization, cell printing, vascularization, integration of cross linking of methods for scaffolding of biomaterials to reproduce and recapitulate complexity in engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 96 publications
(118 reference statements)
0
11
0
Order By: Relevance
“…A second factor helping to increase stability may be a change in the structure of the scaffold. It is known that stem cells can secrete various biologically active substances, for example, cytokines, growth factors, and various inhibitors [46,[65][66][67]. Our studies have demonstrated that ASCs cultivated in the scaffolds under analysis maintain their secretory activity [47,68].…”
Section: Discussionmentioning
confidence: 59%
“…A second factor helping to increase stability may be a change in the structure of the scaffold. It is known that stem cells can secrete various biologically active substances, for example, cytokines, growth factors, and various inhibitors [46,[65][66][67]. Our studies have demonstrated that ASCs cultivated in the scaffolds under analysis maintain their secretory activity [47,68].…”
Section: Discussionmentioning
confidence: 59%
“…In parallel with the choice of cell culture, researchers focused on the conditions for its proliferation [25,[59][60][61]. It was noted that 3D cell culturing repeats the natural conditions of cell proliferation in the body and allows one to obtain a more functional regenerate; as a result, three-dimensional biomimetic structures-scaffolds-were created, which can be considered as one of the main tools for modifying cell culturing conditions.…”
Section: Three-dimensional Environment and Scaffoldsmentioning
confidence: 99%
“…The use of scaffolds in hyaline cartilage regeneration offers a number of advantages: the possibility of reliably fixing the cell-engineered construct (CEC) on the surface of the damaged joint area, protection from significant mechanical stress at the initial stage after implantation, and, most importantly, a natural 3D microenvironment. The 3D structure induces spontaneous cell proliferation in the chondrogenic direction to generate an extracellular matrix characteristic of the hyaline cartilage and drives the synthesis of key proteins, such as type II collagen and aggrecan, thereby preventing cell de-differentiation [40,53,58,61,62].…”
Section: Three-dimensional Environment and Scaffoldsmentioning
confidence: 99%
“…Cells communicate with their environment using different components to regenerate tissues by combining human cells with specific scaffold biomaterials. The biomaterial scaffolds provide templates for tissue regeneration and guide new tissues in their growth [ 4 , 5 ]. A successful approach in tissue engineering and regeneration implies that the combination of these three principles must be able to replace the damaged tissue and enable its function similarly to the original tissue or must be able to stimulate regeneration of the original tissue [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%